Are Padang City Branding Shaping Audience Consciousness: an Semiotics Analysis of Three Padang City Branding - Fitri Adona; Yusnani Yusnani; Sri Nita (Politeknik Negeri Padang, 2018)
One form of city marketing that is currently developing is the provision of city image or city branding. Brands can have 6 levels of understanding namely attributes, benefits, cultural values, personality, and users. Cultural values are very different, especially around socially embedded issues such as status, gender, family, ethics, and customs. City branding helps influence